Workplace Incivility dan Kinerja Dosen di Kota Pontianak: Peran Mediasi Sinisme dan Keterikatan Kerja - JESAJAS, Thea; Hendharsa, Angga; Febriasari, Puty (Kelola: Jurnal Manajemen Pendidikan, 2025)
Incivility in the workplace is not a new phenomenon, particularly in higher education settings, where complex transformations occur due to generational differences in the workforce. This study aims to measure the impact of workplace incivility on work engagement and cynicism, as well as its effects on the job performance of university lecturers in Pontianak. This research adopts an explanatory design to elucidate the causal relationships between variables using quantitative methods. Primary data were obtained by distributing questionnaires to respondents selected through purposive sampling. The study involved 122 lecturers representing various age groups from Baby Boomers, Generation X, Millennials (Generation Y), to Generation Z, to elucidate the responses of each generation to the phenomenon of workplace incivility. The collected data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that work engagement partially mediates the relationship between workplace incivility and job performance, with a significance value of 0.005. Meanwhile, cynicism fully mediates the relationship between workplace incivility and job performance, with a significance value of 0.748.